Core‐Log‐Seismic Integration in Metamorphic Rocks and Its Implication for the Regional Geology: A Case Study for the ICDP Drilling Project COSC‐1, Sweden. (16th March 2021) - Elger, Judith; Berndt, Christian; Kästner, Felix; Pierdominici, Simona; Kück, Jochem; Almqvist, Bjarne S. G.; Juhlin, Christopher; Lorenz, Henning
Abstract: Continental collision causes deformation in the crust along shear zones. However, the physical and chemical conditions at which these zones operate and the deformation processes that enable up to hundreds of km of tectonic transport are still unclear because of the depth at which they occur and the challenges in imaging them. Ancient exhumed collision zones allow us to investigate these processes much better, for example at the COSC‐1 borehole in the central Scandinavian Caledonides. This study combines data from the COSC‐1 borehole with different seismic measurements to provide constraints on the spatial lithological and textural configuration of the Seve Nappe Complex. This is one of the few studies that shows that core‐log‐seismic integration in metamorphic rocks allows to identify the spatial distribution of major lithological units. Especially gamma ray logs in combination with density data are powerful tools to distinguish between mafic and felsic lithologies in log‐core correlation. Our results indicate that reflections along the borehole are primarily caused by compositional rather than textural changes. Reflections in the Seve Nappe Complex are not as distinct as in greater depths but continuous and several of them can be linked to magmatic intrusions, which have been metamorphically overprinted. Their setting indicates that the Seve Nappe Complex consists of the remnants of a volcanic continental margin. Our results suggest that ductile‐deformed middle crustal reflectivity is primarily a function of pre‐orogenic lithological variations which has to be considered when deciphering mountain building processes. Plain Language Summary: Areas where continents collide experience different kind of deformation. However, these processes and the conditions at which they take place are difficult to study because of the great depth at which they occur. Former collision zones that are closer to the surface these days allow the investigation of these processes much better, for example at the COSC‐1 borehole in the central Scandinavian Caledonides. The challenge remains to image the remnant of these processes in high detail but at the same time over a large area. This study combines data from the COSC‐1 borehole with different geophysical measurements to better understand the lithology and structure of the Seve Nappe Complex. We show that the combination of these data allows us to distinguish between rocks from mafic and sedimentary origin. Our results indicate that the geophysical data along the borehole image the change of the composition of the rocks which probably originates from magmatic intrusions and have been overprinted by geological processes, rather than from fracture zones. Key Points: Core‐log‐seismic integration works well with metamorphic rocks in the middle crust Log analysis can distinguish between former mafic and sedimentary lithologies Reflections at COSC‐1 are caused primarily by compositional variation